Neonatal Naso-Oro-Hypopharyngeal Langerhans Cell Histocytosis: Case Report. - AlEidan, A.; Alshamrani, Mohammad; AlGhofaily, Mazen; Alhajji, Ahmed; Ullah , Zaheer; AlQasimi , Mai; AlWallan , Abdulrahman (Jour Med Resh and Health Sci, 2021)
Langerhans cell histiocytosis (LCH) is a rare histiocytic disorder most commonly characterized by single or multiple osteolytic bone lesions demonstrating infiltration with histiocytes having bean-shaped nuclei on biopsy. These histiocytes, along with lymphocytes, macrophages, and eosinophils may infiltrate nearly every organ (most notably the skin, lymph nodes, lungs, thymus, liver, spleen, bone marrow, or central nervous system with the exception of the heart and kidneys). (1) We, hereby, describe a rare case of Naos-Oro-Hypopharyngeal LCH in a neonate.